2018
DOI: 10.3892/etm.2018.7051
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of absolute ethanol combined with n‑butyl cyanoacrylate sclerotherapy in the treatment of Puig's classified advanced venous malformation in children

Abstract: The aim of the present retrospective study was to investigate the clinical safety and efficacy of absolute ethanol combined with n-butyl cyanoacrylate sclerotherapy in the treatment of Puig's classified advanced venous malformation. Sclerotherapy was performed in 121 children (52 males and 69 females; age range, 5 months to 16 years) with venous malformations under general anesthesia between April 2009 and October 2014 at the Department of Interventional Radiology and Vascular Anomalies, Guangzhou Women and Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This demographic is similar to that of previous studies such as Lee et al (318 patients,40.8% male and 59.2% female; average age, 24.9), 9) Su et al (average age, 22.9 years), 10) and Li et al (57% male and 43% female). 11) We used Puig s classification to divide venous malformations into four types. This classification is mainly based on the characteristics of the drainage veins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This demographic is similar to that of previous studies such as Lee et al (318 patients,40.8% male and 59.2% female; average age, 24.9), 9) Su et al (average age, 22.9 years), 10) and Li et al (57% male and 43% female). 11) We used Puig s classification to divide venous malformations into four types. This classification is mainly based on the characteristics of the drainage veins.…”
Section: Discussionmentioning
confidence: 99%
“…This demographic is similar to that of previous studies such as Lee et al (318 patients, 40.8% male and 59.2% female; average age, 24.9), 9 ) Su et al (average age, 22.9 years), 10 ) and Li et al (57% male and 43% female). 11 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a curative efficacy of 93.5% averaged across our cohort’s Puig type VMs is greater than the 70% reported in recent literature, our small cohort is insufficient to establish true statistical significance correlating the ability of balloon implementation in achieving more total sclerosis in type 2 to 4 VMs. 18 Nevertheless, such a trend towards reducing the total number of sclerotherapy sessions due to more complete outflow vein occlusion via balloon inflation should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…17 Li et al recently reported a 70% efficacy following combined ethanol and n-butyl cyanoacrylate sclerotherapy of their cohorts' Puig type VMs, higher than 55% curative rates previously reported in the literature. 18 The aim of sclerotherapy is to induce mural irritation of its respective target with subsequent sclerosis, collapse, and eventual pruning of the malformation. In contrast, as embolotherapy results in primary mechanical occlusion while otherwise maintaining the structural integrity of its target, its minimal utilization is preferred to avoid creation of large areas of firm or potentially palpable lumps in the respective regions of the given malformation.…”
Section: Discussionmentioning
confidence: 99%